2008
DOI: 10.1007/s11510-008-0009-z
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation auto-oscillations in a fluidized bed

Abstract: Oscillations of nonuniform fluidized bed in the slugging regime are considered. A nonlinear onedimensional model of bed oscillations is developed and investigated, including the equations of the bed surface motion and the oscillations of the pressure drop in the bed for the phase of the surface ascent and for the phase of its fall. A quasi-discrete process of the gas escape from the layer with large bubble and the relaxation (discontinuous) type of oscillations of the bed surface and of the pressure, which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Solid lines -calculation of the natural frequency of fluctuations of the bed by ( 5) from the number of half-wavelengths (n) along the diameter of the installation under the assumption that the behavior of standing surface waves of an ideal fluid is analogous to fluctuations of the surface of a fluidized bed. From the graph it can be concluded that, in contrast to formula (4), the standing wave technique [13,14], formula (5), shows that the bed frequencies can vary discretely, depending on the number of half-waves along the installation diameter, but within a constant the number of halfwaves, the frequency will decrease with an increase in the ratio of diameter to height. Calculations in Ansys Fluent show that formula (4) is more accurate when the ratio of the diameter to the height is less than 1, and that with an increase in the ratio of the diameter to the height, the number of half-waves along the diameter grows so intensively that, in parallel with this, a smooth increase in the oscillation frequency occurs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid lines -calculation of the natural frequency of fluctuations of the bed by ( 5) from the number of half-wavelengths (n) along the diameter of the installation under the assumption that the behavior of standing surface waves of an ideal fluid is analogous to fluctuations of the surface of a fluidized bed. From the graph it can be concluded that, in contrast to formula (4), the standing wave technique [13,14], formula (5), shows that the bed frequencies can vary discretely, depending on the number of half-waves along the installation diameter, but within a constant the number of halfwaves, the frequency will decrease with an increase in the ratio of diameter to height. Calculations in Ansys Fluent show that formula (4) is more accurate when the ratio of the diameter to the height is less than 1, and that with an increase in the ratio of the diameter to the height, the number of half-waves along the diameter grows so intensively that, in parallel with this, a smooth increase in the oscillation frequency occurs.…”
Section: Resultsmentioning
confidence: 99%
“…The efficiency of heat and mass transfer processes in BFB is determined by the hydrodynamic parameters of the apparatus, which include the resistance of the gas distributor, the uniformity of fluidization over its area [3] and hydrodynamic interaction between bed and air-plenum chamber [4]. In calculations of the interphase interaction processes in the bed, the size of bubbles and their distribution in the volume of the bed are used, which are determined on the basis of models of selfsustained fluctuations of the bed mass [5][6][7] and the corresponding them dynamic pressure fields [8,9]. Experimental studies show that the appearance and propagation of pressure waves in the bed depends on the mechanism of the exit of gas bubbles to the bed surface [10][11][12].…”
Section: Introductionmentioning
confidence: 99%